Optimalisasi Produktivitas Alat Gali Muat Dan Angkut Untuk Mencapai Target Produksi Batugamping Di PT.Amir Hajar Kilsi Kabupaten Rembang Provinsi Jawa Tengah - dionisius un (Retii, 2021)
Abstrac Mining activities must be adjusted to the production target to be achieved. Limestone production target of PT. Amir Hajar Kilsi of 32,550 Tons/Month. To achieve this target, the company has set a minimum production target of 155 tons/hour of limestone production equipment used. But in reality the productivity of the equipment used has not yet reached 155 Tons/Hour. The purpose of this study was to determine the factors that affect the productivity of digging and loading equipment. Based on observations and research in the field, the actual production of the Sany sy215c excavator is only 119.19 tons/hour. The cause of the actual production has not reached 155 Tons/hour is due to poor work efficiency and a lot of delays in equipment circulation time. To increase the productivity of each equipment can be done by improving work efficiency and reducing the delay in circulation time on each equipment. The actual conveyance cycle time is 561 seconds, so that improvements are made by reducing the loading delay time and dumping maneuvers so as to obtain the repair transport equipment cycle time of 549 seconds. The actual productivity after repair is 166.48 Ton/Hour, or in other words, it has met the desired productivity.